Head-to-head comparison of 68Ga-FAPI-04 PET/CT and 18F-FDG PET/CT in the evaluation of primary digestive system cancer: a systematic review and meta-analysis - Ouyang, Jiqi; Ding, Peiwen; Zhang, Runshun; Lu, Yuexia (Frontiers in Oncology, 2023)
Introduction: Although 18F-FDG PET/CT is widely accepted as a diagnostic tool for detecting digestive cancers, 68Ga-FAPI-04 PET/CT may perform better in detecting gastrointestinal malignancies at an earlier stage. This study aimed to systematically review the diagnostic performance of 68Ga-FAPI-04 PET/CT compared with that of 18F-FDG PET/CT in primary digestive system cancers. Methods: In this study, a comprehensive search using the PubMed, EMBASE, and Web of Science databases was performed to identify studies that met the eligibility criteria from the beginning of the databases to March 2023. We assessed the quality of the relevant studies with the QUADAS-2 method using the RevMan 5.3 software. Sensitivity and specificity were calculated using bivariate random effects models, and heterogeneity was assessed with the I2 statistic and meta-regression analysis using the R 4.22 software. Results: A total of 800 publications were identified in the initial search. Finally, 15 studies comprising 383 patients were included in the analysis. The pooled sensitivity and specificity of 68Ga-FAPI-04 PET/CT were 0.98 (95% CI, 0.94-1.00) and 0.81 (95% CI, 0.23-1.00), whereas those of 18F-FDG PET/CT were 0.73 (95% CI, 0.60-0.84) and 0.77 (95% CI: 0.52–0.95), respectively. 68Ga-FAPI-04 PET/CT performed better for specific tumours, particularly in gastric, liver, biliary tract, and pancreatic cancers. Both imaging modalities had essentially the same diagnostic efficacy in colorectal cancer. Conclusions: 68GaFAPI-04 PET/CT showed a higher diagnostic ability compared to 18F-FDG PET/CT in terms of diagnosing primary digestive tract cancers, especially for gastric, liver, biliary tract, and pancreatic cancers. The certainty of the evidence was high due to the moderately low risk of bias and low concern regarding applicability. However, the sample size of the included studies was small and heterogeneous. More high-quality prospective studies are needed to obtain higher-quality evidence in the future. Systematic review registration The systematic review was registered in PROSPERO (CRD42023402892).